Flux line interactions in conventional and high critical transition temperature superconductors. - Lalonde, Richard. (University of Ottawa (Canada), 1990)
We have developed a novel experimental approach for the study of the interaction of sheets of non parallel flux lines in hysteric type II superconductors. We continuously monitor the evolution of the components of the magnetic flux density $\Vert$ and $\perp$ to $H\sb{a}$ (i.e. $\langle B\sb{z}\rangle$ and $\langle B\sb{y}\rangle$) as $H\sb{a}$ is raised to various intensities, and then reduced to zero. In our investigation of a high $T\sb{c}(YBa\sb{2}Cu\sb{3}O\sb{7-x}$) ceramic, $H\sb{a}$ exceeded $H\sb{*}$, the first full penetration field. We applied the phenomenological Clem general critical state model to the analysis of our extensive observations. A computer program was developed to solve the four coupled differential equations of this theory with appropriate physical constraints for the situations prevailing in our experiment. This analysis provides detailed insight into the evolution of the intricate configurations of the magnetic flux density $\vec B$(x), the critical current density, $\vec J$(x), and electric field $\vec E$(x) patterns as the injected and trapped flux lines are made to interact, unpin, migrate and undergo flux cutting processes. The model is seen to generate the variety of complicated measured curves of $\langle B\sb{y}\rangle$ and $\langle B\sb{z}\rangle$ vs $H\sb{a}$ very satisfactorily. (Abstract shortened by UMI.)
Keywords: Physics, Electricity and Magnetism.